Remembering the past and imagining the future: Identifying and enhancing the contribution of episodic memory. (July 2016) - Schacter, Daniel L; Madore, Kevin P
Recent studies have shown that imagining or simulating future events relies on many of the same cognitive and neural processes as remembering past events. According to the constructive episodic simulation hypothesis, such overlap indicates that both remembered past and imagined future events rely heavily on episodic memory: future simulations are built on retrieved details of specific past experiences that are recombined into novel events. An alternative possibility is that commonalities between remembering and imagining reflect the influence of more general, non-episodic factors such as narrative style or communicative goals that shape the expression of both memory and imagination. We consider recent studies that distinguish the contributions of episodic and non-episodic processes in remembering the past and imagining the future by using an episodic specificity induction—brief training in recollecting the details of a past experience—and also extend this approach to the domains of problem solving and creative thinking. We conclude by suggesting that the specificity induction may target a process of event or scene construction that contributes to episodic memory as well as to imagination, problem solving, and creative thinking.